Outplay Your Weaker Self: A Mixed-Methods Study on Gamification to Overcome Procrastination in Academia - Kirchner-Krath, Jeanine; Schmidt-Kraepelin, Manuel; Schöbel, Sofia; Ullrich, Mathias; Sunyaev, Ali; von Korflesch, Harald F.O. (CHI '24: Proceedings of the CHI Conference on Human Factors in Computing Systems, 2024)
Procrastination is the deliberate postponing of tasks knowing that it will have negative consequences in the future. Despite the potentially serious impact on mental and physical health, research has just started to explore the potential of information systems to help students combat procrastination. Specifically, while existing learning systems increasingly employ elements of game design to transform learning into an enjoyable and purposeful adventure, little is known about the effects of gameful approaches to overcome procrastination in academic settings. This study advances knowledge on gamification to counter procrastination by conducting a mixed-methods study among higher education students. Our results shed light on usage patterns and outcomes of gamification on self-efficacy, self-control, and procrastination behaviors. The findings contribute to theory by providing a better understanding of the potential of gamification to tackle procrastination. Practitioners are supported by implications on how to design gamified learning systems to support learners in self-organized work.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Gameful design; Gamification; Higher education; Learning; Procrastination; Task management